ANALISIS STRATEGI E-COMMERCE PADA PT. SPADA INOVASI DIGITAL MENGGUNAKAN METODE IT BALANCED SCORECARD - Abdullah, Muhammad; Widarto, Nabilla Umniyah; Zuhdi, Rafi; Puspitaningrum, Ari Cahaya; Fitriani, Laqma Dica (Program Studi Sistem Informasi, Universitas Banten Jaya, 2024)
The use of information systems is one of the IS/IT investments in a company. Information systems can certainly improve company performance, but many information systems have not been implemented optimally, and do not meet the company's vision, mission and goals. This research was conducted with the aim of making strategic planning for the implementation of the E-Commerce information system at PT. Beware of Digital Innovation. The strategic plan was developed based on the IT Balanced method. Data collection was carried out through interviews, then the data obtained was subjected to SWOT analysis, then mapped into the IT Balanced Scorecard. This research produces strategic recommendations that companies can implement, including: 1) from an operational excellence perspective, companies need to determine IS/IT employees and regular maintenance; 2) user orientation perspective, companies need to adjust the interface design according to customer wishes and provider manuals as a template for system use; 3) future orientation perspective, companies need to recruit employees which can be done with background checks; 4) from a business contribution perspective, companies need to maintain and improve service quality. It is hoped that the results of this research can improve the quality of PT Waspada Innovation Digital's e-commerce.